IMPACT OF SUBSIDIES ON THE FINANCIAL POSITION OF LOCAL GOVERNMENT BUDGETARY ESTABLISHMENTS IN POLAND - Piotr Sołtyk (Polityki Europejskie, Finanse i Marketing)
The article presents an assessment of the impact of subsidies received from the budget of a local government unit on the financial situation of local government budgetary establishments in Poland. As a result of the change in the financial law in 2009, budgetary establishments operate only at the local government level. Despite the fact that legislators decided that the sphere of tasks of budgetary establishments is strictly defined in the law, it is justified to assess the impact of the subjective subsidy transferred from the local government budget on the generated revenues. The article verifies the hypothesis, that the amount of the subsidy depends on the generated revenues. The hypothesis was verified using Pearson’s linear correlation coefficient vector and Kruskal-Wallis analysis of variance. All analyses were performed with the Statistica v.12 package.